Molecular attachment to a microscope tip: inelastic tunneling, Kondo screening, and thermopower - Tuerhong, Rouzhaji; Boero, Mauro; Bucher, Jean-Pierre (Beilstein Journal of Nanotechnology, 2019)
The vibrational excitation related transport properties of a manganese phthalocyanine molecule suspended between the tip of a scanning tunneling microsope (STM) and a surface are investigated by combining the local manipulation capabilities of the STM with inelastic electron tunneling spectroscopy. By attachment of the molecule to the probe tip, the intrinsic physical properties similar to those exhibited by a free standing molecule become accessible. This technique allows one to study locally the magnetic properties, as well as other elementary excitations and their mutual interaction. In particular a clear correlation is observed between the Kondo resonance and the vibrations with a strong incidence of the Kondo correlation on the thermopower measured across the single-molecule junction.
Keywords: inelastic electron tunneling; molecular quantum dot; Kondo physics; single molecule; thermopower; tunnel junction

(untitled) - Lafferentz, L.; Ample, F.; Yu, H.; Hecht, S.; Joachim, C.; Grill, L. (Science, 2009)

(untitled) - Temirov, R.; Lassise, A.; Anders, F. B.; Tautz, F. S. (Nanotechnology, 2008)

(untitled) - Aradhya, S. V.; Venkataraman, L. (Nat. Nanotechnol., 2013)

(untitled) - Reecht, G.; Lotze, C.; Sysoiev, D.; Huhn, T.; Franke, K. J. (ACS Nano, 2016)

(untitled) - Stipe, B. C.; Rezaei, M. A.; Ho, W. (Science, 1998)

(untitled) - Gimzewski, J. K.; Joachim, C.; Schlittler, R. R.; Langlais, V.; Tang, H.; Johannsen, I. (Science, 1998)

(untitled) - Chong, M. C.; Reecht, G.; Bulou, H.; Boeglin, A.; Scheurer, F.; Mathevet, F.; Schull, G. (Phys. Rev. Lett., 2016)

(untitled) - Otte, A. F.; Ternes, M.; von Bergmann, K.; Loth, S.; Brune, H.; Lutz, C. P.; Hirjibehedin, C. F.; Heinrich, A. J. (Nat. Phys., 2008)

(untitled) - Park, J.; Pasupathy, A. N.; Goldsmith, J. I.; Chang, C.; Yaish, Y.; Petta, J. R.; Rinkoski, M.; Sethna, J. P.; Abruña, H. D.; McEuen, P. L.; Ralph, D. C. (Nature, 2002)

(untitled) - Yu, L. H.; Keane, Z. K.; Ciszek, J. W.; Cheng, L.; Tour, J. M.; Baruah, T.; Pederson, M. R.; Natelson, D. (Phys. Rev. Lett., 2005)

(untitled) - Osorio, E. A.; O'Neill, K.; Wegewijs, M.; Stuhr-Hansen, N.; Paaske, J.; Bjørnholm, T.; van der Zant, H. S. J. (Nano Lett., 2007)

(untitled) - Rakhmilevitch, D.; Korytár, R.; Bagrets, A.; Evers, F.; Tal, O. (Phys. Rev. Lett., 2014)

(untitled) - Gao, L.; Ji, W.; Hu, Y. B.; Cheng, Z. H.; Deng, Z. T.; Liu, Q.; Jiang, N.; Lin, X.; Guo, W.; Du, S. X.; Hofer, W. A.; Xie, X. C.; et al. (Phys. Rev. Lett., 2007)

(untitled) - Heinrich, B. W.; Iacovita, C.; Brumme, T.; Choi, D.-J.; Limot, L.; Rastei, M. V.; Hofer, W. A.; Kortus, J.; Bucher, J.-P. (J. Phys. Chem. Lett., 2010)

(untitled) - Tsukahara, N.; Shiraki, S.; Itou, S.; Ohta, N.; Takagi, N.; Kawai, M. (Phys. Rev. Lett., 2011)

(untitled) - Mugarza, A.; Robles, R.; Krull, C.; Korytár, R.; Lorente, N.; Gambardella, P. (Phys. Rev. B, 2012)

(untitled) - Kezilebieke, S.; Amokrane, A.; Abel, M.; Bucher, J.-P. (J. Phys. Chem. Lett., 2014)

(untitled) - Minamitani, E.; Fu, Y.-S.; Xue, Q.-K.; Kim, Y.; Watanabe, S. (Phys. Rev. B, 2015)

(untitled) - Kügel, J.; Karolak, M.; Senkpiel, J.; Hsu, P.-J.; Sangiovanni, G.; Bode, M. (Nano Lett., 2014)

(untitled) - Liu, L.; Yang, K.; Jiang, Y.; Song, B.; Xiao, W.; Song, S.; Du, S.; Ouyang, M.; Hofer, W. A.; Castro Neto, A. H.; Gao, H.-J. (Phys. Rev. Lett., 2015)

(untitled) - Tuerhong, R.; Ngassam, F.; Watanabe, S.; Onoe, J.; Alouani, M.; Bucher, J.-P. (J. Phys. Chem. C, 2018)

(untitled) - Jaklevic, R. C.; Lambe, J. (Phys. Rev. Lett., 1966)

(untitled) - Hellwig, R.; Paintner, T.; Chen, Z.; Ruben, M.; Seitsonen, A. P.; Klappenberger, F.; Brune, H.; Barth, J. V. (ACS Nano, 2017)

(untitled) - Ternes, M.; Heinrich, A. J.; Schneider, W.-D. (J. Phys.: Condens. Matter, 2009)

(untitled) - Yu, L. H.; Keane, Z. K.; Ciszek, J. W.; Cheng, L.; Stewart, M. P.; Tour, J. M.; Natelson, D. (Phys. Rev. Lett., 2004)

(untitled) - Parks, J. J.; Champagne, A. R.; Hutchison, G. R.; Flores-Torres, S.; Abruña, H. D.; Ralph, D. C. (Phys. Rev. Lett., 2007)

(untitled) - Fernández-Torrente, I.; Franke, K. J.; Pascual, J. I. (Phys. Rev. Lett., 2008)

(untitled) - Ohta, N.; Arafune, R.; Tsukahara, N.; Kawai, M.; Takagi, N. (J. Phys. Chem. C, 2013)

(untitled) - Brumboiu, I. E.; Haldar, S.; Lüder, J.; Eriksson, O.; Herper, H. C.; Brena, B.; Sanyal, B. (J. Chem. Theory Comput., 2016)

(untitled) - Liu, Z.; Zhang, X.; Zhang, Y.; Jiang, J. (Spectrochim. Acta, Part A, 2007)

(untitled) - Ben-Zvi, R.; Vardimon, R.; Yelin, T.; Tal, O. (ACS Nano, 2013)

(untitled) - Paaske, J.; Flensberg, K. (Phys. Rev. Lett., 2005)

(untitled) - Boese, D.; Fazio, R. (Europhys. Lett., 2001)

(untitled) - Rincón-García, L.; Evangeli, C.; Rubio-Bollinger, G.; Agraït, N. (Chem. Soc. Rev., 2016)

(untitled) - Widawsky, J. R.; Darancet, P.; Neaton, J. B.; Venkataraman, L. (Nano Lett., 2012)

(untitled) - Sierra, M. A.; López, R.; Sánchez, D. (Phys. Rev. B, 2017)

(untitled) - Sto/vneng, J. A.; Lipavský, P. (Phys. Rev. B, 1990)